Tornando-se um Assentado Rural do MST: uma análise psicossocial das idas e vindas do homem do campo - Santos, Maria Augusta Costa dos (2005)
This dissertação had for objective to understand as if agricultural one gives the process to become one seated, arguing the directions of this process for the citizens of this research, aiming at to raise subsidies to reflect on its potentiality citizen eor of perverse inclusion. For the referenciais of the Partner-historical Psychology of Vygotsky and the Nucleus of Psicossociais Studies of the Dialectic had been in such a way used Exclusion Social inclusion. The research was carried through in a Nesting, located in the Zone of Mata of the State of Alagoas, when 65 living citizens of this nesting had been interviewed in the first stage and in the second stage nine citizens, of which only seven had been valid for the purposes of the research and construction of histories of life of the citizens, since the interviewed others had been monossilábicos in its answers. The analysis was guided by the theoretical referencial created by Vygotsky, searching subtexto (affective-volitional base) of it speaks of the interviewed ones to understand the directions and meanings of if becoming one seated agricultural one of the MST. With this analytical procedure one arrived it the following units of felt: Work, Education, Religion and Leisure, all they perpassadas by the unit of bigger direction that is the land. From the results it was arrived conclusion that the citizens had searched the MST for survival necessity, e had been potencializados for the action during all the period of fight for the land and construction of the nesting.When becoming seated agricultural, they were desmobilizaram for the action, with the attitude to wait for the other for the resolution of the problems of the nesting, with few spaces and moments of collective convivência, with the productive work and commercialization of the agricultural products almost always restricted to the lot and the family (in detriment of the collective production). The only factor of mobilization is the religion. All these results point with respect to a form of perverse and precarious inclusion by means of the agricultural nesting, where they lack convivência spaces, allotment and affection; assistance technique adjusted for the production and commercialization of the products; precarious access to the system of public health; unglued education of the reality of the nesting; precarious access to the nesting through roads without asphalt and badly conserved and predominance of the directions proclaimed for religious institutions, that they take them to wait, now, for the land promised in the sky.